(untitled) (World Science, 2021)
Intrahepatic cholestasis of pregnancy (idiopathic jaundice of pregnancy, recurrent familial jaundice of pregnancy) is a benign familial disease manifesting itself in the gestational period in itching and (or) jaundice. As a rule, the disease is observed in the 3rd trimester of pregnancy, that is in the 28th-30th week, and may disappear by itself a few days after labor and recur during future pregnancies. The aim of this research is to study the role and factors of vascular homeostasis regulation in women with infertility treated with assisted reproductive technologies (ART) and with concomitant intrahepatic cholestasis. Intrahepatic cholestasis is characterized by the damage of endothelial cells of hepatic sinusoids, changes in the intrahepatic hemodynamics, increased production of cytokines and free radicals. The processes of angiogenesis in the liver are also closely connected with the functional capacity of endothelium. The L-arginine level in blood was measured using the photometric method based. The homocysteine level was measured by the enzymatic cycling method. To measure the level of placental growth factor (PGF) in blood plasma samples, we used the immunochemical method. The research has found especially severe complications in the course of pregnancy after ART in those women with intrahepatic cholestasis whose placentas developed under the conditions of endothelial dysfunction from the very beginning of pregnancy. So, these factors may be early prognostic markers of severe obstetrical and perinatal disorders in women with induced pregnancy and hepatobiliary disorders.